2021
DOI: 10.26565/2312-4334-2021-2-06
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassic Models of the Dissipative Regime of Instability and Superradiation of a Quantum Radiator System

Abstract: The paper discusses the similarity between dissipative generation and superradiance regimes for systems of excited quantum emitters placed in an open cavity. In the case of the existence of a resonator field due to reflections from the ends of the system, a dissipative generation regime is usually realized. In this case, the decrement of oscillations in the waveguide in the absence of radiators turns out to be greater than the increment of the arising instability of the system of radiators placed in the resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…It is important to note that at a relatively low density of oscillators, their wave functions do not overlap [15]; therefore, they can affect each other only by their own radiation fields. And here the increments of the processes and the maximum achievable amplitudes of the field of these two regimes practically coincide [16].…”
mentioning
confidence: 58%
“…It is important to note that at a relatively low density of oscillators, their wave functions do not overlap [15]; therefore, they can affect each other only by their own radiation fields. And here the increments of the processes and the maximum achievable amplitudes of the field of these two regimes practically coincide [16].…”
mentioning
confidence: 58%
“…Let us show that, on the one hand, it is necessary to take into account the intrinsic field of the emitters, because it qualitatively affects all the characteristics of the mode of oscillation generation. On the other hand, a comparison of the achievable amplitudes of the resonator field and the superradiance field for one system of emitters showed that they are of the same order [6]. This is an additional argument for the need to take into account the eigenfields of the emitters in the resonator.…”
Section: Introductionmentioning
confidence: 96%
“…If this resonator is filled with an active medium, a dissipative waveguide excitation regime is also possible, in which quantum oscillators interact only with the resonator field, and there is no direct interaction between them [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that at a relatively low density of oscillators, their wave functions do not overlap. Quantum oscillators at their low density can affect each other only by electromagnetic fields of their own radiation [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation